'Being there': rhythmic diversity and working students. Issue 5 (4th July 2022) - Taylor, Alison
ABSTRACT: Although universities promote undergraduate degrees as journeys of exploration and reflection, they are also viewed by students as investments in professional careers. This paper draws on a study of 57 second-year students at a research-intensive university in Canada to explore the subjective dimensions of time and school-work rhythms in students' everyday lives. Data suggest that most students expect to work hard, now and in the future, although their backgrounds influence perceptions of the kind of hard work required, and the magnitude and certainty of returns. Students are future-oriented and participation in term-time work is seen as a way of training for future work lives. This training involves adapting bodies to the temporal logics and rhythms of university studies and workplaces. The interplay of rhythms is experienced by some students as harmonious or 'eurhythmic', and by others as discordant or 'arrhythmic'. The extent of discord is related to differences in students' work and studies, differences in their time horizons and value calculations, and differences in family background and resources. This paper contends that understanding students' sense-making in regard to chrono-logics and work-school rhythms is important for building a vision for higher education that better supports human flourishing.